Rehabilitative management of pelvic fractures needs to be further optimized - Zehua Li; Dilihumaer Maimaitiming; Leqi Sun; Haoran Wang; Weixi Xiong (PAGEPress Publications, 2021)
We read with interest the review by Piccione et al. into the rehabilitative management of patients with pelvic fracture (PF). This review adds to our knowledge about the significance and indispensability of early multidisciplinary intervention in PF. From our perspective, however, potential bias might be caused by several unanswered questions. The uncertain methodological process and the unclear definition could misguide the rehabilitation strategies while still in dispute. Therefore, further high-quality studies should be conducted to optimize the multidisciplinary rehabilitation of patients with PF.